REPORT OF THE COMMITTEE ON EDUCATIONAL STANDARDS. - Bastable, Charles W.; Glos, Raymond E.; Johnson, Charles E.; Kessler, L.M.; Miller, Herbert E.; Nelson, Harold G.; Taggart, Herbert E.; White, John A.; Moyer, C.A. (The Accounting Review, 1964)
The article presents a report of the Committee on Educational Standards. The purpose of accounting education is to prepare students for careers in accounting and in related fields and to prepare them to deal effectively with problems they will face as practicing members of their profession and as responsible citizens of the social and economic community in which they live. In recent years, the pattern of collegiate education for business in the U.S. has received considerable attention. The resulting re-examination of objectives, evaluations of course content, and revisions of curricula have had a major impact on accounting education as an element in the business school program. As the accounting function in modern society grows, the role of the accountant inevitably becomes larger and more important. The demand for well-educated accountants is currently high and promises to remain strong in the foreseeable future. The purpose of this study is to formulate some guidelines pointing to the educational standards that should prevail in any institution of higher education that offers degree programs involving a major in accounting, to the end that one or more degrees in accounting will indicate a standard of educational background and qualification for a professional field.